2021
DOI: 10.1016/j.isci.2021.102035
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarettes compromise the gut barrier and trigger inflammation

Abstract: Summary E-cigarette usage continues to rise, yet the safety of e-cigarette aerosols is questioned. Using murine models of acute and chronic e-cigarette aerosol inhalation, murine colon transcriptomics, and murine and human gut-derived organoids in co-culture models, we assessed the effects of e-cigarette use on the gut barrier. Histologic and transcriptome analyses revealed that chronic, but not acute, nicotine-free e-cigarette use increased inflammation and reduced expression of tight junction (TJ)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 71 publications
1
21
0
1
Order By: Relevance
“…Intestinal organoids were isolated and cultured following methods optimized previously ( Sharma et al., 2021 ) and explained here briefly. Human ileum biopsies were collected from healthy adult male and female subjects undergoing routine colonoscopy for colon cancer screening using the protocol approved by the Human Research Protection Program Institutional Review Board (Project ID# 190105).…”
Section: Star★ Methodsmentioning
confidence: 99%
“…Intestinal organoids were isolated and cultured following methods optimized previously ( Sharma et al., 2021 ) and explained here briefly. Human ileum biopsies were collected from healthy adult male and female subjects undergoing routine colonoscopy for colon cancer screening using the protocol approved by the Human Research Protection Program Institutional Review Board (Project ID# 190105).…”
Section: Star★ Methodsmentioning
confidence: 99%
“…This systemic pro-inflammatory status might also have an impact on the gut microbiota composition, as suggested by available studies on the impact of e-cigarette use on animals’ gut microbiota and on oral microbiota composition in humans [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…These activities included acting as an online information source about tobacco-control legislative developments (including for CA local ordinances, state legislation/referendum, and federal legislation), inserting discourse and opinion against tobacco-control policy with information about policy, and possibly misrepresenting scientific information about the potential harms of ENDS and vaping. For example, posts observed included those arguing against a study that indicates that chemicals found in e-cigarettes disrupts the gut barrier and triggers inflammation in the body leading to potential harm [ 42 ]; and they also questioned the veracity of the methodology of studies that detected potentially harmful chemicals in e-cigarettes [ 43 ]. Further, these community groups make specific calls to action to mobilize against tobacco-control policies (e.g., inviting online users to political mobilization events, asking them to take direct action against tobacco-control policies, etc.).…”
Section: Discussionmentioning
confidence: 99%